KOMPOSISI HASIL TANGKAPAN SIDAT (Anguilla spp) DI SUNGAI LUAS DAN SUNGAI KINAL, PROVINSI BENGKULU - Gillang Fernando; Ronny Irawan Wahju; Am Azbas Taurusman (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2021)
The fishing activity of eel fish for daily consumption has been carried out by the local people in the Kaur Regency. However, the data related to the species of the eel fish, catch structure, and the eel fishing ground in Kaur Regency is still very limited, especially in the Luas River and Kinal River. Data and information on the eel fisheries in Kaur Regency are expected to be used as basic information in sustainable use of the eel fisheries. This study aims to analyze the catch composition of the eel caught and to determine the eel fishing ground for both rivers. Experimental fishing using eel hand line was carried out from June to August 2021 in Luas River and Kinal River, Kaur Regency, Bengkulu. The composition of catch eel only one species of eel, namely Anguilla marmorata with ano-dorsal ratio of 14.05-18.23%. The A. marmorata eel was caught at every station in both rivers. The Shannon – Wiener (H') diversity index of the catches at all stations in both rivers was relatively similar, ranging from 1.14 to 1.69. The eel fishing grounds in the Luas river and Kinal river are divided into 3 areas: estuary, mid- part of the rivers, and upstream area. Keywords: Anguilla marmorata, catch composition, eel, Kinal river, Luas river.